Dexamethasone is Associated With a Lower Risk of the Progression of Thoracic Aortic Calcification in Breast Cancer Survivors - Lei, Juan; Liu, Aiting; Ma, Yujia; Shi, Guangzi; Han, Feng; Jiang, Wenlong; Zhou, Yongqiao; Zhang, Chao; Liu, Yimin; Huang, Xiaobo; Huang, Hui; Chen, Jie (Frontiers in Pharmacology, 2021)
Background and Purpose: Breast cancer survivors have an increased cardiovascular risk, and vascular calcification is the pathological basis of cardiovascular disease. Some factors that affect the progression of thoracic aortic calcification (TAC) in survivors are unclear, and this study aims to explore the relationship between dexamethasone or radiotherapy and the progression of TAC in survivors. Materials and Methods: This study included 189 female patients with breast cancer, and they were divided into the progression and non-progression TAC groups. Radiation or dexamethasone doses, and related laboratory parameters were collected. Results: The cumulative dose of dexamethasone was higher (40 [10-180] mg versus 180 [80-270] mg, P<0.001), and the cycle was longer (4 [1-6] cycles versus 6 [4-8] cycles, P<0.001) in the non-progression TAC group. The cumulative dose (r=-0.303, P<0.001) and cycle (r=-0.357, P<0.001) of dexamethasone were negatively correlated with the level of increased TAC Agatston scores in survivors. Logistic regression analysis showed that dexamethasone was a protective factor for the progression of TAC (P=0.029, odds ratio=0.263, 95% confidence interval=0.08 to 0.872). However, there wasn’t significant relationship between radiotherapy, radiation dose, follow-up time and the progression of TAC (all P>0.05). In addition, aorta volume was positively correlated with the level of increased TAC Agatston scores in intensity modulated radiation therapy (r=0.460, P<0.001). Conclusions: Dexamethasone is associated with a lower risk of the progression of TAC in breast cancer survivors, and there’s no correlation between radiotherapy and progression of TAC, but the aorta volume may be a predictor of the severity of progression of TAC.